Perilaku Pemeliharaan Gigi Tiruan Sebagian Lepasan Resian Akrilik - Sharren Teguh; Arlyn Laurensia (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Tooth loss is a dental and oral health problem that often occurs in the wider community with a multi-factorial process involving dental caries and periodontal disease. The prevalence of tooth loss increases with age, especially in Indonesia. Dentures are one of the treatments that can be used to improve appearance, phonetics, and to replace missing teeth. The Resta questionnaire was modified and tested for validity and reliability so that it could be used in this study to evaluate the maintenance behavior of removable partial dentures. Goals: To find out the overview of removable partial dentures maintenance behavior in acrylic resin removable partial dentures wearers in RSGM-P Faculty of Dentistry Trisakti University. Methods: The type of this research is descriptive observational with a cross-sectional study design. This research was conducted by distributing the modified Resta questionnaire to 96 respondents who had received acrylic resin removable partial dentures treatment by dentists and dental students at RSGM-P Faculty of Dentistry Trisakti University. Result: As many as 51% of respondents had the behavior of maintaining removable partial dentures which were in the sufficient category. Conclusion: The results obtained are that many of the acrylic resin removable partial dentures wearers at the RSGM-P Faculty of Dentistry Trisakti University have quite good at removable partial dentures maintenance behavior can be due to the patient's fairly good knowledge of the dentures post-insertion instructions given by dentists or dental students.